Integrating Transformative and Servant Leadership with Islamic Values: Implications for Local Government Effectiveness in Indonesia - Bekti, Herijanto; Pancasilawan, Ramadhan; Komara, Syifa Rachmania (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
Leadership plays a crucial role in determining the direction and success of local government in Indonesia. This study aims to analyze the relevance and implications of the concepts of transformative leadership and servant leadership from an Islamic perspective on local governance. Both leadership models emphasize moral values, empathy, and empowerment, which align with Islamic leadership principles such as justice (al-'adl), trustworthiness, and community service. In the context of local government, the application of these values ​​is expected to strengthen bureaucratic integrity, increase public trust, and create policy innovations oriented toward the interests of the people. This study used a qualitative method with a descriptive-analytical approach, with secondary data obtained from scientific literature, religious documents, and public policy sources. The results indicate that the application of transformative leadership and servant leadership principles based on Islamic values ​​has a positive influence on the effectiveness of local government in Indonesia. Leaders who integrate a transformative vision with a spirit of service have been shown to improve bureaucratic performance, strengthen public trust, and encourage innovation in public services and sustainable development. Islamic values ​​such as justice, trustworthiness, and moral responsibility serve as the foundation that strengthens transparency, accountability, and a service-oriented approach to the community.